If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + 2 = 3y + 5 Reorder the terms: 2 + 4y = 3y + 5 Reorder the terms: 2 + 4y = 5 + 3y Solving 2 + 4y = 5 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 2 + 4y + -3y = 5 + 3y + -3y Combine like terms: 4y + -3y = 1y 2 + 1y = 5 + 3y + -3y Combine like terms: 3y + -3y = 0 2 + 1y = 5 + 0 2 + 1y = 5 Add '-2' to each side of the equation. 2 + -2 + 1y = 5 + -2 Combine like terms: 2 + -2 = 0 0 + 1y = 5 + -2 1y = 5 + -2 Combine like terms: 5 + -2 = 3 1y = 3 Divide each side by '1'. y = 3 Simplifying y = 3
| 12y=1+2 | | x+7=3(4+x)-7x | | 3x-1y=163 | | -2y=12+x | | -a(a-1)=0 | | 10x-5=3y | | X+20x=180 | | 73=4n-7 | | 4(d-3)=-8 | | 2(6+s)+s-10+s=100 | | 2.5x(x+2)+4.5x=1.5(x-4) | | 3x+x-3=25 | | 0.2(n-5)=0.3n+6-4+0.1n | | -.55(x+2)=4.4 | | -8=(3-d)4 | | -2x+4y=-40 | | 1600=p(1+0.06) | | 5m-15-20m+5= | | (3x+6)(2x-12)(x+8)=0 | | -4y-2x=-8 | | -1.5x+y=320 | | 6f-13=24f-11 | | 6f-13=24f | | 1.4x+2y=800 | | 5*x-9+2*x+3=90 | | -4(x-2)+6x-15-x(4-3)=14-3(x+2)+7x-4 | | 0=-16 | | 380=2(w)(w+20) | | 5*4-9+2*4+3= | | 11+10=-8 | | 9+.75x=.875x-10 | | 5(4-3c)-6(2c+1)= |